Difference fractal surfaces poured earth floors Tamaulipas / Diferencia fractal en superficies de tierra vertida con suelo de Tamaulipas - Edgardo Jonathan Suárez Dominguez; Yolanda Guadalupe Aranda Jiménez (Contexto: Revista de la Facultad de Arquitectura Universidad Autónoma de Nuevo León, 2013)
Poured earth is a sustainable construction and economically feasible technique to develop in Tamaulipas, by the materials availability and traditional manufacturing procedures uses. There are several variables to be considered in these elements for their properties, among them it can be found roughness and porosity analysis which are important because they are related to material mechanical resistance and durability. This study aimed to characterize solid surfaces using fractal dimension to know its uniformity and porosity, compared with a concrete surface. Solids were obtained from poured earth of two combinations of soils stabilized with cement from the state of Tamaulipas. We found that a surface of a sample, obtained with ground, is more uniform than poured concrete surface, and that fractal dimension is higher while porosity increases; results suggest that this is because of the presence of clay in the poured earth mixtures.